Maringá: A British Garden City in the tropics - Macedo, Joseli (ELSEVIER SCI LTD, 2011)
Maringá, located in southern Brazil, deserves to be studied because of its uniqueness. It is one of a few cities designed according to Garden City principles and developed by the British in Brazil as part of a regional network of cities connected by rail. The city also distinguishes itself from several other cities in Brazil because it is the seat of a metropolitan region that, despite having had the highest growth of all metropolitan regions in the state of Paraná in the 1990s, has managed to prevent informal settlements from developing within its boundaries. This profile describes the creation and growth of this young, mid-sized city, the design principles followed by its founders, and the political and socioeconomic reasons for its successful development. A critical evaluation of regional planning efforts and shortcomings of a Garden City-inspired design raises issues and describes challenges to be faced by Maringá in the near future. The article concludes that Maringá’s responses to these challenges will determine what kind of future the city will have. Ultimately, a concerted effort to keep its exceptional characteristics will need to be made if its citizens are to maintain the quality of life they have enjoyed during the first half-century of its existence.